Comparative Study of Regulatory Mechanisms for Pectinase Production by Erwinia carotovora subsp. carotovora and Erwinia chrysanthemi - Hiroyuki Matsumoto; Pongphen Jitareerat; Yasuhiro Baba; Shinji Tsuyumu (Molecular Plant-Microbe Interactions, 2003)
The production of pectinase, the major virulence determinant of soft-rot Erwinia species, is controlled by many regulatory factors. We focused on the major regulatory proteins, KdgR, CRP, Pir, and PecS, characterized mainly in E. chrysanthemi, and tested for their presence and function in the control of pectate lyase (Pel) and polygalacturonase (Peh) production in E. carotovora subsp. carotovora. Homologues of kdgR and crp but not of pir and pecS were detected by Southern blot analyses in E. carotovora subsp. carotovora. In fact, KdgR and CRP homologues of E. carotovora subsp. carotovora had high amino acid identities to those of E. chrysanthemi, including a complete match of the hypothetical helix-turn-helix DNA-binding motif. However, in Western blot analyses using anti-Pir (E. chrysanthemi) antibodies, a cross-reacting protein was present in both Erwinia species, although Pel production in E. carotovora subsp. carotovora was not further stimulated by adding plant extract into the medium containing PGA (polygalac-turonic acid) in which hyperinduction by Pir has been reported in E. chrysanthemi EC16. When plasmids that contained each of these regulatory genes from E. chrysanthemi were introduced into E. carotovora subsp. carotovora, Pel production was controlled as predicted from their roles in E. chrysanthemi, except for PecS. PecS exerted a positive control in E. carotovora subsp. carotovora, in contrast to a negative control in E. chrysanthemi. DNA-binding assays demonstrated that KdgR, CRP, Pir, and PecS of E. chrysanthemi and KdgR and CRP homologues of E. carotovora subsp. carotovora could bind to the promoter regions of pel-1, pel-3, and peh of E. carotovora subsp. carotovora. Taken together, KdgR and CRP homologues of E. carotovora subsp. carotovora may regulate Pel and Peh production as in E. chrysanthemi. However, the presence of Pir and PecS homologues in E. carotovora subsp. carotovora was not identified in this study, though these proteins of E. chrysanthemi were functional on the promoter regions of the pectinase genes of E. carotovora subsp. carotovora.